Implementation in the “real world” of an evidence-based social and emotional learning program for teachers: effects on children social, emotional, behavioral and problem solving skills - Gaspar, Maria Filomena; Seabra-Santos, Maria; Relvão, Joana; Pimentel, Mariana; Homem, Tatiana; Azevedo, Andreia Fernandes; Moura-Ramos, Mariana (Frontiers in Psychology, 2024)
Introduction The delivery of social and emotional learning (SEL) programs that are developmentally school-based and evidence-based has the potential to benefit many children, and as such, greater efforts are needed to disseminate these programs more widely within the community. The Incredible Years® Teacher Classroom Management (IY-TCM) has shown promising results when applied by teachers in preschool centers and primary schools, as seen in several randomized control trials conducted worldwide, including in Portugal. Methods The current study presents a model of the implementation of the program within the framework of a nationwide initiative undertaken in Portugal: the Academias Gulbenkian do Conhecimento. Additionally, results of the program’s impact on children were explored using ANOVA, which compared pre- to post- treatment outcomes. To assess which factors affected the efficacy of the intervention, moderation analyses were conducted using the MEMORE macro. Ninety teachers and 535 children (2 to 10 years old) were assessed. Results Results revealed that children showed significant increases in social and emotional skills (e.g., social adjustment, empathy) and significant reductions in problem behavior when assessed by their teachers, and in social-cognitive problem solving strategies as evaluated by a set of problem-solving tasks. Moderation analyses showed that, in general, interaction effects were not found, meaning that the intervention was effective for almost all conditions. Nevertheless, significant moderation effects were found for factors pertaining to the child and the mother with respect to pro-social and emotional skills (children who benefited most from the intervention exhibited more behavioral difficulties at the baseline according to the teachers’ perceptions and had mothers without a university degree; children attending primary school took less benefit from the intervention than those attending pre-school). Discussion The findings contribute both to the reinforcement of the effectiveness of the IY-TCM program as a universal intervention in “real world” schools and to the development of some guidelines for the promotion of effective scaling up and sustainability of program effects.